ISSUES OF DELIMITATION AND MAPPING OF THE SANGZOR RIVER BASIN BASED ON A BASIN APPROACH - Dursinovich, Qosimov Nurmuxamad (ANTIS PUBLISHER, 2025)
Objective: This study aims to analyze the Sangzor River basin as a distinct geosystem by delineating its geographical and administrative boundaries and assessing its internal structural hierarchy. Method: The research employs a basin approach supported by Geographic Information System (GIS) and remote sensing technologies to determine the spatial extent, sub-basin classification, and natural resource utilization within the Sangzor basin. Results: The findings reveal that the Sangzor River basin, located in the Middle Zarafshan natural geographic district and spanning the Jizzakh and Samarkand regions, consists of 78 identified sub-basins categorized into first-order basins. The study provides precise geographic coordinates, demonstrates the interconnection between tributaries originating from the Morguzar and Chumqor mountains, and identifies key environmental characteristics influencing basin dynamics. Novelty: This research contributes to the field by integrating a basin-geosystem perspective with advanced GIS-based delineation techniques, offering an updated methodological framework for assessing river basin structures and natural resource management in arid and semi-arid regions of Central Asia.